Feasibility of energy justice: Exploring national and local efforts for energy development in Nepal. (June 2017) - Islar, Mine; Brogaard, Sara; Lemberg-Pedersen, Martin
Abstract: The energy justice framework serves as an important decision-making tool in order to understand how different principles of justice can inform energy systems and policies. The realization of the urgency of providing modern energy technology and services particularly to rural areas has prompted both the Nepalese government and development institutions to focus on community-run renewable energy facilities. It is argued that off-grid and micro-scale energy development offers an alternative path to fossil-fuel use and top-down resource management as they democratize the grid and increase marginalized communities' access to renewable energy, education and health care. However, Nepal's energy development is also heavily influenced by demands from the fast-growing economies of neighboring countries such as China and India. As a result, this article evaluates the Nepalese national energy policies by applying the key aspects of the energy justice framework and showing the feasibility constraints due to geopolitical and biophysical factors to the implementation of energy just policies in this developing country context. The empirical evidence is derived from interviews during a one-month fieldwork in the Lalitpur and Katmandu districts of Nepal, site-visits, discourse analysis of expert statements, government policies and newspaper articles as well literature review on peer-review articles. Highlights: Energy justice framework can be used as a decision-making tool. Energy transitions need to be understood from multiple perspectives. Justice principles may face geopolitical, biophysical and ethical feasibility constraints. The implementation of energy justice principles requires attention to the problem of agency.